School Based Intervention on Overweight in Children: A Meta Analysis - Nurlaili, Riftiani Nikmatul; Dewi, Yulia Lanti Retno; Adriyani, Rita Benya (Journal of Maternal and Child Health, 2020)
Background: Overweight is a serious nutritio